Audience and Revenue Concentration in Lithuanian Media Markets (2008–2019) - Jastramskis, Deimantas; Plepytė-Davidavičienė, Giedrė (Information & Media, 2022)
The article examines the change in audience and revenue concentration in the Lithuanian television, radio, internet, and newspaper markets in 2008–2019, as well as discusses the factors that determined the changes in media concentration and market structure. The study revealed that without any special measures to regulate media concentration in Lithuania, all four media revenue markets (television, radio, internet, and newspapers) have become highly concentrated. In terms of audience (circulation) concentration, the concentration of newspaper and television markets was divided between un concentrated and moderately concentrated areas, the radio audience was moderately concentrated, and the audience of internet news websites was highly concentrated. The results of the analysis show a tendency for audience concentration in media markets to be generally lower than income market concentration. Therefore, when legally defining a dominant position in media markets, it is recommended to set a lower value for audience share than for revenue market share.